Strenghts of Character of Personal Growth: Structure and Relations with the Big Five in the Brazilian Context - Ana Paula Porto Noronha; Cristian Zanon (Paidéia (Ribeirão Preto), 2018)
Abstract The structure of character strengths and virtues in different cultural contexts across the globe has failed to recover the six-factor solution originally proposed by Peterson and Seligman. This study aims to assess the structure of the Character Strengths Scale, a test created to assess character strengths and virtues and the association between these strengths and personality factors in the Brazilian context. The sample was made up of 981 undergraduate students (60.5% female) aged between 17 and 26 years (M = 20.7, SD = 2.2), who responded the Character Strengths Scale and Personality Factors Battery. Exploratory factor analysis indicated that the three-factor solution was the most theoretically appropriate, identifying the following factors: Intellectual Strengths, Intrapersonal Strengths and Collectivism, and Transcendence. Regression analysis showed that three personality factors (conscientiousness, extraversion and neuroticism) are relevant predictors of these strengths, explaining a considerable amount of variance. The implications of the findings are presented, suggesting that high levels of neuroticism may impair the flourishing of strengths.